Plan promocional inclusivo de los derechos de las personas con discapacidad cantón Quevedo. Año 2015 - Rodríguez Barre, José Ignacio (2015)
This project aims to create an inclusive promotional plan for the rights of people with disabilities in the canton Quevedo; To meet this objective the following methods were used: A) an analysis of the situation was conducted by interviewing people with disabilities and citizenship achieving a comprehensive assessment of the issue, it helped us to continue the investigation. B) A SWOT analysis for the qualities and characteristics of persons with disabilities was conducted. C) Market research was done through a survey people Quevedo Canton to identify promotional purposes to be used in this plan. D) Promotional plan considered in two stages proceeded to design: the first is a training campaign and talk for persons with disabilities who are in the workplace; as well as enterprises and public and private institutions in order to inform and make known the rights of persons with disabilities, encourage the inclusion of the same in the political and economic social field work; and the second is a promotional campaign by media, such as television, radio, print and billboard advertising with the aim of positioner slogan, about the rights of people with disabilities and encourage the person on the inclusion of people with disabilities. D) the spot, spots, advertisements and billboards are also designed. E) Finally he drew the respective conclusions. It should be noted that throughout the process of research and analysis and value could qualify factors identified opportunities and threats as well as their strengths and weaknesses and the results have been principals in the development of this plan. The promotional plan has three strategic promotional purposes, five individual analysis, a general analysis, four specific objectives, one general and an introduction. Finally the implementation of this plan that will raise the acceptance and inclusion of people with disabilities is recommended.